On the 90th birthday of Inna Semnovna Zbandut, literary editor of Oftalmologicheskii Zhurnal (Ukrainian Journal of Ophthalmology, 2025)
Every morning for the last sixty-seven years, Inna Semenovna Zbandut, a thin little intellectual-looking woman and the irreplaceable copy editor of our journal since 1978, goes along the French Boulevard to her place of work at the institute. She does not believe that she could live without going along this path, the path to the temple of science created by a great scientist, Acad. Vladimir Petrovich Filatov. This path of life was a gift of fortune to her.